Calidad de atención y su relación con la fidelización de los pasajeros de la aerolínea Viva Air en la ciudad de Iquitos, año 2018 - Guevara Gonzales, Mercedes Lizbeth (2021)
The present study seeks to analyze the relationship between the quality of care and the loyalty of the passengers of the viva air airline in the city of Iquitos, since it was an applied - correlational - cross-sectional research and a non-experimental design, since through this, it was sought to contribute to the theoretical knowledge, through the analysis and description of the variables, as well as to determine the level of relationship that exists between the two, showing that the phenomena have not been deliberately manipulated, but that they are presented as they are. develop in their natural state, so 369 customers were taken as a sample to whom a survey consisting of 10 questions for the evaluation of the quality of care and one of 13 questions for the evaluation of passenger loyalty was applied. Concluding in this way that the quality of care and the loyalty of the passengers of the Viva Air airline in the city of Iquitos are related, since a Spearman Rho correlation coefficient of 0.62283 was obtained with a significance level of 0.003. Likewise, it was identified that the behavior of the attention was classified as regular because not all the collaborators are kind and polite with the clients, however the collaborators listen to the client's discharges, but do not fully commit to looking for an immediate solution, which is why customers do not feel an attachment to the company and indicate that they are not so satisfied.